Juristas autoritários versus juristas liberais o debate estabelecido no campo jurídico brasileiro 1964-1969 - Lotúmolo, Marinês Bernardinelli (2007)
The analysis of the trajectory of the jurists in the period between 1964 and 1969 requires the identification of diverse chains of the same jurists. Three main chains of jurists in this period had been identified the authoritarian, the liberal and the nationalists jurists. For this analysis it took in consideration the position and ideas politicians of each one of the chains. After that, it was searched to identify the trajectory of each one of the groups, in special the observation of the increasing hegemony of the chain of authoritarian jurists, that directly remained in contact with the military governments after April of 1964. While the construction of a new government happened, the performance of the authoritarian jurists became more frequently, permitting a great debate with the idea of the other group of jurists the liberal. The performance of the authoritarian chain occurred in reason much more of the necessity of internal control to the military sphere than in relation to the manifestations of the society.